A cerebellopontine angle mouse model for the investigation of tumor biology, hearing, and neurological function in NF2-related vestibular schwannoma - Chen, Jie (Nat Protoc, 2019)
Neurofibromatosis type II (NF2) is a disease that lacks effective therapies. NF2 is characterized by bilateral vestibular schwannomas (VSs) that cause progressive and debilitating hearing loss, leading to social isolation and increased rates of depression. A major limitation in NF2 basic and translational research is the lack of animal models that allow the full spectrum of research into the biology and molecular mechanisms of NF2 tumor progression, as well as the effects on neurological function. In this protocol, we describe how to inject schwannoma cells into the mouse brain cerebellopontine angle (CPA) region. We also describe how to apply state-of-the-art intravital imaging and hearing assessment techniques to study tumor growth and hearing loss. In addition, ataxia, angiogenesis, and tumor–stroma interaction assays can be applied, and the model can be used to test the efficacy of novel therapeutic approaches. By studying the disease from every angle, this model offers the potential to unravel the basic biological underpinnings of NF2 and to develop novel therapeutics to control this devastating disease. Our protocol can be adapted to study other diseases within the CPA, including meningiomas, lipomas, vascular malformations, hemangiomas, epidermoid cysts, cerebellar astrocytomas, and metastatic lesions. The entire surgical procedure takes ~45 min per mouse and allows for subsequent longitudinal imaging, as well as neurological and hearing assessment, for up to 2 months.